2022
DOI: 10.23922/jarc.2021-069
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Result of the Mucopexy-Recto Anal Lifting Method for Hemorrhoids in Comparison with Ligation and Excision, and Aluminum Potassium Sulfate and Tannic Acid Sclerotherapy

Abstract: The outcomes of Mucopexy-Recto Anal Lifting (MuRAL) in hemorrhoid surgery were compared with ligation and excision (LE), and aluminum potassium sulfate and tannic acid sclerotherapy (ALTA). In this study, we conducted a 3-year follow-up study of MuRAL (380 cases) and compared it with LE (1417 cases) and ALTA (541 cases) performed at the same period. Operative time, mean hospital stay, postoperative pain, postoperative complications, and recurrence were compared and examined retrospectively. The mean operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Multivariate analysis also found that suspension ligation was the protective factor for postoperative adverse events. These results are consistent with previous studies [15]. Therefore, suspension ligation can reduce the occurrence of postoperative adverse events, especially for severe prolapse of internal hemorrhoids.…”
Section: Follow-up Outcomessupporting
confidence: 93%
See 1 more Smart Citation
“…Multivariate analysis also found that suspension ligation was the protective factor for postoperative adverse events. These results are consistent with previous studies [15]. Therefore, suspension ligation can reduce the occurrence of postoperative adverse events, especially for severe prolapse of internal hemorrhoids.…”
Section: Follow-up Outcomessupporting
confidence: 93%
“…The suspension ligation mentioned in this paper is a new ligation method based on above theory. By ligating the mucous membrane above the dentate line, the prolapsed anal cushion can move upward, as a result, the prolapse degree of internal hemorrhoids can be relieved and the incidence of postoperative adverse events such as bleeding, edema and pain et al, can be reduced [15]. In this study, we found that the proportion of using suspension ligation in grade III internal hemorrhoids group was signi cantly higher than that in grade I and II internal hemorrhoids groups, the postoperative adverse events was signi cantly lower than that in other two groups.…”
Section: Follow-up Outcomesmentioning
confidence: 99%